Manajemen Nyeri Pada Pasien Dispepsia Dengan Nyeri Akut di Ruang Melati RSUD Tais Kabupaten Seluma - Reza Purwasih; Hermansyah Hermansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Dyspepsia is a common gastrointestinal disorder often accompanied by acute epigastric pain that requires comprehensive nursing management. This case study aimed to describe the implementation of pain management nursing care in patients with dyspepsia and acute pain at Melati Ward, RSUD Tais, Seluma Regency. A descriptive case study design was conducted on two patients diagnosed with dyspepsia. Nursing care was provided through the stages of assessment, nursing diagnosis, planning, implementation, and evaluation over a period of 3×24 hours. The nursing interventions focused on non-pharmacological pain management, including warm compress therapy using a Warm Water Zack (WWZ), deep breathing relaxation techniques, and guided imagery. The evaluation results demonstrated a decrease in pain scale, improvement in nonverbal pain responses, increased appetite, improved sleep quality, and stabilization of vital signs in both patients. In conclusion, evidence-based non-pharmacological pain management nursing interventions are effective as complementary therapies in reducing acute pain in patients with dyspepsia and can be applied independently by patients and their families.